Reaksi Pasar Antara Penurunan dan Penahanan Bi Rate Terhadap Saham Perbankan di Bursa Efek Indonesia Tahun 2025 - Muhammad Aslam Widad (Fakultas Ekonomi dan Bisnis, 2026)
This study examines how the Indonesian capital market responds to announcements of changes in the BI Rate issued by Bank Indonesia throughout 2025. The background of this study is the divergence in findings from previous research regarding the impact of interest rates on stock prices, as well as the limited number of studies that specifically examine the banking subsector’s response to interest rate policies. This study aims to test the difference in Average Abnormal Return (AAR) before and after BI-Rate announcements, as well as to compare the Cumulative Average Abnormal Return (CAAR) between interest rate cut and hold policies. The method used is an event study with a quantitative approach. The sample consists of 41 banking stocks selected purposively from companies listed on the Indonesia Stock Exchange during 2025, with an event window of 11 trading days. The analysis was conducted using nonparametric tests, namely the Wilcoxon Signed Rank Test and the Mann–Whitney Test, as the data were not normally distributed. The results show that market reactions are heterogeneous, with only some periods yielding a significant AAR. Cumulatively, the rate hold policy showed a significant CAAR, whereas the rate cut did not. However, no significant difference in CAAR was found between the two types of policies. These findings indicate that market responses are influenced not only by the direction of interest rate changes but also by perceptions of the policy context, with the market tending to be more responsive to signals of stability.
FINALISASI oleh Agus 2026 Juni 08
Keywords: BI-Rate; Saham Perbankan; Abnormal Return; Event Study